What are the constraints and opportunities for HIVST scale‐up in Africa? Evidence from Kenya, Malawi and South Africa. Issue 1 (20th March 2015) - van Rooyen, Heidi; Tulloch, Olivia; Mukoma, Wanjiru; Makusha, Tawanda; Chepuka, Lignet; Knight, Lucia C; Peck, Roger B; Lim, Jeanette M; Muturi, Nelly; Chirwa, Ellen; Taegtmeyer, Miriam
Abstract : Introduction: HIV self‐testing (HIVST) has the potential to increase uptake of HIV testing among untested populations in sub‐Saharan Africa and is on the brink of scale‐up. However, it is unclear to what extent HIVST would be supported by stakeholders, what policy frameworks are in place and how variations between contexts might influence country‐preparedness for scale‐up. This qualitative study assessed the perceptions of HIVST among stakeholders in three sub‐Saharan countries. Methods: Fifty‐four key informant interviews were conducted in Kenya ( n =16), Malawi ( n =26) and South Africa ( n =12) with government policy makers, academics, activists, donors, procurement specialists, laboratory practitioners and health providers. A thematic analysis was conducted in each country and a common coding framework allowed for inter‐country analysis to identify common and divergent themes across contexts. Results: Respondents welcomed the idea of an accurate, easy‐to‐use, rapid HIV self‐test which could increase testing across all populations. High‐risk groups, such as men, Men who have sex with men (MSM), couples and young people in particular, could be targeted through a range of health facility and community‐based distribution points. HIVST is already endorsed in Kenya, and political support for scale‐up exists in South Africa and Malawi. However, several caveats remain. Further research, policy and ensuing guidelines should consider how to regulate, market and distribute HIVST, ensure quality assurance of tests and human rights, and critically, link testing to appropriate support and treatment services. Low literacy levels in some target groups would also need context‐specific consideration before scale up. World Health Organization (WHO) policy and regulatory frameworks are needed to guide the process in those areas which are new or specific to self‐testing. Conclusions: Stakeholders in three HIV endemic sub‐Saharan countries felt that HIVST will be an important complement to existing community and facility‐based testing approaches if accompanied by the same essential components of any HIV testing service, including access to accurate information and linkages to care. While there is an increasingly positive global policy environment regarding HIVST, several implementation and social challenges limit scale‐up. There is a need for further research to provide contextual and operational evidence that addresses concerns and contributes to normative WHO guidance.